The Impact Factor of Costs to the Tax System - Challoumis, Constantinos (Journal of Entrepreneurship, Business and Economics, 2020)
This paper is about the costs of the enterprises to the tax system. Thence, we have an analysis of the impact factor of the tax revenues of the countries subject to the costs of companies on the tax system. Thereupon from the view of the level of influence of the enterprises which participate in controlled transactions of transfer pricing to the global tax revenue, it is plausible to identify the impact factor of costs, when there exists that factor with the case which that factor is avoided. The impact factor of costs in combination with the tax revenues is determined through the Q.E. method and the R.B.Q. model. Inasmuch as, is defined as the behavior of the tax system subject to the capital of the tax system. Then a quantitative simulation is used as a methodology for this work, to define the impact of costs on the enterprises. Research paper Keywords: transfer pricing; costs; tax revenue; transactions Reference to this paper should be made as follows: Challoumis, C. (2020). The Impact Factor of Costs to the Tax System, Journal of Entrepreneurship, Business and Economics , 8 (1), 1–14.